2015
DOI: 10.1177/1040638715595062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of litter prevalence of Mycoplasma hyopneumoniae in preweaned piglets utilizing an antemortem tracheobronchial mucus collection technique and a real-time polymerase chain reaction assay

Abstract: The swine industry currently lacks validated antemortem methods of detecting baseline herd prevalence of Mycoplasma hyopneumoniae. The focus of our study was to evaluate alternative antemortem detection techniques and to determine baseline litter prevalence in preweaned pig populations utilizing the selected technique and a real-time polymerase chain reaction (qPCR) assay. Preliminary data was analyzed on weaned piglets with evidence of respiratory disease (n = 32). Five sample types (antemortem nasal swab, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
1
28
4
3
Order By: Relevance
“…Tracheo-bronchial sampling was performed as previously described [ 6 , 7 ]. Briefly, TBS samples were obtained following restraint of the piglets with a nose snare, and subsequent use of a mouth opener.…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tracheo-bronchial sampling was performed as previously described [ 6 , 7 ]. Briefly, TBS samples were obtained following restraint of the piglets with a nose snare, and subsequent use of a mouth opener.…”
Section: Case Presentationmentioning
confidence: 99%
“…Piglets can become infected with M. hyopneumoniae during the suckling period and many studies have shown M. hyopneumoniae -positive animals from weaning onwards [ 2 – 7 ]. Moreover, once infected with M. hyopneumoniae , animals can excrete the pathogen over a long period of time, with total clearance lasting till 254 days post-infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hard to carry out retrospective experiments when the nasal swabs are stored for a long time. Furthermore, nasal swab sample collection is inconvenient in live pigs for their curved nasal cavities, and swabs were found to be not reliable at individual pig level [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to carry out retrospective experiments. Furthermore, nasal swab sample collection is inconvenient in live pigs for their curved nasal cavities, and swabs were found to be not reliable at individual pig level[14][15][16]. Therefore, development of an IgG-ELISA method which can differentiate convalescent and hyperimmune sera is easy to get serum samples…”
mentioning
confidence: 99%